Network Structures for Asset Return Co-Movement: Evidence From the Chinese Stock Market - Shi, Huai-Long; Chen, Huayi (Frontiers in Physics, 2022)
This paper focuses on the detailed network structure of the comovement for asset returns. Based on the Chinese sector indices and Fama-French five factors, we conduct return decomposition and construct a minimum spanning tree (MST) in terms of the rank correlation among raw return, idiosyncratic return, and factor premium. With the adoption of rolling window analysis, we examine the static and the time-varying characteristics associated with the MST(s). We find that: 1) A star-like structure is presented for the whole sample period, in which market factor MKT acts as the hub node; 2) The star-like structure changes during the periods for major market cycles. The idiosyncratic returns for some sector indices would be disjointed from MKT and connected with their counterparts and other pricing factors; 3) The effectiveness of pricing factors are time-varying, and investment factor CMA seems redundant in the Chinese market. Our work provides a new perspective for the research of asset comovement, and the test of the effectiveness of empirical pricing factors.